Feeling godly : religious affections and Christian contact in early North America - Wigginton, Caroline; Van Engen, Abram C., 1981- (University of Massachusetts Press, 2021)
"In 1746, Jonathan Edwards described his philosophy on the process of Christian conversion in A Treatise Concerning Religious Affections. For Edwards, a strict Congregationalist, true conversion is accompanied by a new heart and yields humility, forgiveness, and love-affections that work a change in the person's nature. But, how did other early American communities understand religious affections and come to recognize their manifestation? Feeling Godly brings together well-known and highly regarded scholars of early American history and literature, Native American studies, African American history, and religious studies to investigate the shape, feel, look, theology, and influence of religious affections in early American sites of contact with and between Christians. While remaining focused on the question of religious affections, these essays span a wide range of early North American cultures, affiliations, practices, and devotions, and enable a comparative approach that draws together a history of emotions with a history of religion. In addition to the volume editors, this collection includes essays from Joanna Brooks, Kathleen Donegan, Melissa Frost, Stephanie Kirk, Jon Sensbach, Scott Manning Stevens, and Mark Valeri, with an afterword by Barbara H. Rosenwein"--